Pengaruh Iklan Dan Harga Terhadap Minat Beli Penumpang Pada Maskapai Lion Air Di Bandar Udara Internasional Pattimura Ambon - Talbia Elewarin; Arif Fakhrudin (Jurnal Kajian dan Penelitian Umum, 2023)
Passenger buying interest will increase influenced by one factor, namely advertising. The higher the advertisement that is promoted, the higher the interest or interest of the passengers towards the advertisement. Apart from advertising, one of the factors that influence buying interest is price. High buying interest can be formed by the price offered by service or product providers. This study aims to determine the effect of advertising and prices on the purchase intention of passengers on Lion Air Airlines at Ambon Pattimura International Airport. This study uses a quantitative approach. The population in this study were Lion Air airline service users at Pattimura Ambon International Airport. The sample in this study was calculated using the slovin formula, namely 100 samples. Data collection methods used are questionnaires and literature studies. [26/7 10.52] .: High purchase intention can be formed by the price offered by service or product providers. The research was conducted at Ambon Pattimura Airport in August 2022. The data analysis technique used consisted of instrument tests, namely validity tests, reliability tests and multiple linear regression tests as well as hypothesis testing consisting of T tests, F tests, and Determination Coefficient Tests . The results of this study are that advertising partially influences purchase intention with t table of 1.66, where t count X1 is 4.120 meaning that for the advertising variable t count > t table, 4.120 > 1.66. The price variable has a partial effect on buying interest because the T count of the X2 variable is 4.856, meaning that for the advertising variable t count>t table, 4.856> 1.66. The advertising and price variables together or simultaneously have an effect on purchase intention, as evidenced by a significance value of <0.001 <0.05, then Ho is rejected and Ha is accepted, meaning that the independent variables have a significant effect on the dependent variable. The calculated F value for the variable product quality and price is 57.474 for a 5% error in the 2-party test, the F table is 3.09. If F count > F table, the effect between advertising and price on buying interest is obtained, the F count is 57.474 > F table 3.09. This means that there is a positive influence between advertising and price on buying interest on Lion Air at Pattimura Ambon International Airport. The relationship between advertising and price on purchase intention is 54.2%, while the remaining 45.8% is explained by other variables not examined in this study.